Fundamental rights and principles. Liber amicorum Pieter van Dijk (Antwerpen, 2013)
"Pieter van Dijk has devoted his working life to the theory and practice of fundamental rights and principles. Therefore, it may not come as a surprise that his liber amicorum is devoted to these values. Many of his friends and (former) colleagues from – inter alia – the Council of State of the Netherlands, the European Court of Human Rights in Strasbourg, the European Commission for Democracy through Law of the Council of Europe (the Venice Commission) and the Joint Court of Justice of Aruba, Curaçao, Sint Maarten and of Bonaire, Sint Eustatius and Saba have contributed to this volume. They have analyzed fundamental rights and principles from various perspectives, including preconditions for safeguarding fundamental rights, the interaction between the Strasbourg, Luxembourg and national courts and constitutional review. "